Effect of different doses of gadolinium contrast agent on clinical outcomes in MS. Issue 1 (January 2019) - Ackermans, Nathalie; Taylor, Carolyn; Tam, Roger; Carruthers, Robert; Kolind, Shannon; Kang, Heejun; Freedman, Mark S; Li, David KB; Traboulsee, Anthony L
Objective: The objective of this paper is to evaluate potential dose-dependent adverse effects of gadolinium-based contrast agents (GBCAs) on MS progression. Methods: Outcomes from a cohort of 612 secondary progressive MS (SPMS) patients, enrolled in a two-year, placebo-controlled (negative) trial assessing the efficacy of MBP8298, were acquired. Patients received one to four (infrequent cohort; IFR) or 5–11 (frequent cohort; FR) GBCA injections between week 4 and week 104. The primary outcome was the change in Expanded Disability Status Scale (EDSS) and time to confirmed EDSS progression. Secondary outcomes included the changes in the Multiple Sclerosis Functional Composite (MSFC), Timed 25-Foot Walk (T25FW), 9-Hole-Peg Test (9HPT), and Paced Auditory Serial Addition Test (PASAT) from baseline to week 104. Results: The 512 IFR and 100 FR participants showed no differences in baseline demographics or disease history. The mean change from baseline to week 104 in EDSS was +0.21 (IFR) and +0.13 (FR); MSFC –0.38 (IFR) and –0.14 (FR); T25FW +1.28 (IFR) and +0.55 (FR); 9HPT –0.06 (IFR) and –0.08 (FR); and PASAT +0.22 (IFR) and +0.20 (FR). The FR to IFR progression hazard ratio equaled 0.68 ( p = 0.09). There were no significant differences in any of the outcomes between the two cohorts. Conclusion: There were no differences in the disability progression measures between the two cohorts, indicating that gadolinium does not result in greater clinical worsening in SPMS after a two-year period.